Supervision During Rehabilitation Programme Following Anterior Cruciate Ligament Reconstruction: A Systematic Review of Literature - Darain, H.; Shah, S. Z. A.; Muhammad, F.; Al-kitani, A. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2016)
Background: The term ‘supervision’ during musculoskeletal rehabilitation programmes is frequently used in literature. However, there is lack of agreement in the literature regarding clearly defining the term ‘supervision’ and its components. Therefore, this review was carried out to identify components of supervision reported in clinical trial previously carried out on rehabilitation programmes following anterior cruciate ligament reconstruction and define the term clearly.Methods: A review of literature regarding supervision during rehabilitation programme following anterior cruciate ligament reconstruction was undertaken (Jan 2005 until December 2014). Searches in electronic database including AMED, BNI, CINAHL, EMBASE, Health Business Elite, HMIC, MEDLINE, and PsycINFO were carried out for supervision during anterior cruciate ligament rehabilitation. Keywords included anterior cruciate ligament, supervision, structured and unstructured rehabilitation were used to search for the literature.Results: Inconsistencies in defining the term supervision during anterior cruciate ligament rehabilitation were found amongst the clinical trials carried out on supervision following anterior cruciate ligament reconstruction. In some clinical trials, supervision was associated with the environment where rehabilitation programme was delivered. In contrast, in other trials, supervision was associated with the number of physiotherapy sessions received by the patients in hospitals or other clinical settings included clinics.Conclusion: Based on the findings of this review it may be concluded that supervision during rehabilitation programme following anterior cruciate ligament may be associated with a number of factors. Presences of physiotherapists during rehabilitation sessions, well-controlled environment and interaction amongst physiotherapists and patients have been reported core component for supervision.
Keywords: rehabilitation; anterior cruciate ligament; supervision; Physiotherapie; Physical medicine